The Effect of Rewards and Job Satisfaction on Organizational Citizenship Behavior (OCB) of Lecturers at Panca Sakti University Bekasi - Uza Sukmana; Gunawan Gunawan; Luluh Abdilah; Ardin Ardin; Muhammad Ridhwan (UNIVERSITAS SERAMBI MEKKAH, 2022)
Organizational Citizenship Behavior (OCB) is extra-role behavior displayed by employees beyond their formal job descriptions, carried out voluntarily without considering certain awards or rewards, with indicators: (1) altruism (helping others), (2) conscientiousness (role is more than the minimum standard), (3 ) sportsmanship (sportsmanship), (4) courtesy (respect for others), (5) civic virtue (responsibility). The purpose of this study was to obtain information about the effect of reward and job satisfaction on the organizational citizenship behavior of lecturers at Panca Sakti University (UPS) Bekasi. This type of research is quantitative with a survey method at Panca Sakti University (UPS) Bekasi. This research was conducted to all lecturers at Panca Sakti University Bekasi using a survey method with path analysis used in hypothesis testing. A sample of 83 people was selected using the Slovin formula. The results of the study conclude: (1) There is a direct positive effect of reward on OCB. (2) There is a direct positive effect of job satisfaction on OCB. (3) There is a direct positive effect of reward on job satisfaction.